Interventions to reduce impaired driving and traffic injury - Sleet, D.; Howat, Peter; Elder, R.; Maycock, B.; Baldwin, G.; Shults, R. (Birkhäuser Basel, 2009)
This review characterizes the effectiveness of various interventions to prevent impaired driving and reduce traffic injury and death. Interventions are considered within the ecological/health promotion framework, and include: 1) economic interventions, 2) organizational interventions, 3) policy interventions, and 4) health education interventions, including the use of media, school and community education and public awareness programs. Alcohol or drug-impaired driving arises from complex and multiple and interrelated causes. Therefore, prevention efforts will benefit from approaches that rely on a combination of interventions, including educational, behavioral, environmental, and policy approaches. Effective approaches strengthen the skills and capabilities of individuals to take action and the capacity of groups or communities to act collectively to exert control over the determinants of impaired driving. There is strong evidence for the effectiveness of some interventions, including economic and retailer interventions, alcohol taxation, reducing alcohol availability, legal and legislative strategies, and strategies addressing the servers of alcohol, such as server liability and server intervention. There is also evidence for the effectiveness of sobriety checkpoints, lower BAC laws, minimum legal drinking age laws, and supportive media promotion programs. Other interventions with moderate evidence of effectiveness include restricting alcohol advertising and promotion, community mobilization efforts, and ignition interlocks in vehicles of convicted drink-drive offenders. Health education by itself has insufficient evidence for effectiveness, as is also the case with passive server training programs, school drug and alcohol education programs, and health and safety warnings. Taken together, educational, behavioral, environmental and policy approaches to reducing impaired driving using all four components of the ecological/health promotion model are likely to be the most effective. © 2009 Birkhéuser Verlag/Switzerland.